Risk management practices in sport in independent schools in Gauteng - Van Tonder, Ilze (2014)
M.Phil (Sport Management) === Physical Education and sport has a natural place in education whether the approach is formal or informal. Providing learners with the opportunity to play sport at school and to participate in Physical Education ensure that they receive education that addresses the body, mind and spirit. Participation in sport and physical activities in the education environment involves, next to enjoyment, a range of risks. Unfortunately, incidents of injuries and accidents that could have been prevented do occur. These may lead to allegations ofnegligence on the part of a coach, official or even a spectator. It is an educator's duty to ensure that in all matters pertaining to children, including participation in sport and physical activities, the principle of acting in the best interests of the child must take precedence. Proper safety practices and procedures should be implemented by the educator and the school in order to prevent injuries. Risk management is one of the methods by which sport educators can provide the safest possible environment for their participants. This is necessary not only to comply with legal requirements but also to demonstrate sound educational principles that support learnercentered education. This study sought to identify the key problems surrounding the safety of learners engaged in physical activities in the context of sport, Physical Education and recreation in South African independent schools. It analyzed the .qualifications and experience of sport and Physical Education teachers as well as educators' knowledge of risk management practices. An assessment was made about the extent to which risk management procedures were implemented in various schools in order to prevent injuries from occurring.. The study was conducted from a positivistic paradigm and the design comprised a survey. The primary data was gathered by the use of a questionnaire. Secondary data was obtained using literature studies describing risk management, the law in sport and education as well as the management ofsport in schools. The study has established that in general, safety practices and procedures at independent schools in Gauteng are implemented in a prudent and responsible manner. In some schools and with some aspects improvements can still be made but the overall status appears professional and promising. It has been established that independent schools demonstrate good practice with regard to the aspects of insurance, safety measures, supervision of staff members and learners, instruction, equipment, facilities, policies and procedures...